Construction and characterization of bacterial artificial chromosomes harboring the full-length genome of a highly attenuated vaccinia virus LC16m8 - Yoshikawa, Tomoki (PLoS One, 2018)
LC16m8 (m8), a highly attenuated vaccinia virus (VAC) strain, was developed as a smallpox vaccine, and its safety and immunogenicity have been confirmed. Here, we aimed to develop a system that recovers infectious m8 from a bacterial artificial chromosome (BAC) that retains the full-length viral genomic DNA (m8-BAC system). The infectious virus was successfully recovered from a VAC-BAC plasmid, named pLC16m8-BAC. Furthermore, the bacterial replicon-free virus was generated by intramolecular homologous recombination and was successfully recovered from a modified VAC-BAC plasmid, named pLC16m8.8S-BAC. Also, the growth of the recovered virus was indistinguishable from that of authentic m8. The full genome sequence of the plasmid, which harbors identical inverted terminal repeats (ITR) to that of authentic m8, was determined by long-read next-generation sequencing (NGS). The ITR contains x 18 to 32 of the 70 and x 30 to 45 of 54 base pair tandem repeats, and the number of tandem repeats was different between the ITR left and right. Since the virus recovered from pLC16m8.8S-BAC was expected to retain the identical viral genome to that of m8, including the ITR, a reference-based alignment following a short-read NGS was performed to validate the sequence of the recovered virus. Based on the pattern of coverage depth in the ITR, no remarkable differences were observed between the virus and m8, and the other region was confirmed to be identical as well. In summary, this new system can recover the virus, which is geno- and phenotypically indistinguishable from authentic m8.